2014
DOI: 10.1186/cc13997
|View full text |Cite
|
Sign up to set email alerts
|

Interest of low-dose hydrocortisone therapy during brain-dead organ donor resuscitation: the CORTICOME study

Abstract: IntroductionCirculatory failure during brain death organ donor resuscitation is a problem that compromises recovery of organs. Combined administration of steroid, thyroxine and vasopressin has been proposed to optimize the management of brain deceased donors before recovery of organs. However the single administration of hydrocortisone has not been rigorously evaluated in any trial.MethodsIn this prospective multicenter cluster study, 259 subjects were included. Administration of low-dose steroids composed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 30 publications
0
26
0
4
Order By: Relevance
“…A more recent prospective multicenter cluster study of 208 neurologically deceased adults has replicated these results and further trialed steroid replacement therapy (50 mg bolus of hydrocortisone, followed by 10 mg per hour continuous infusion). 54 Of the 121 patients for whom ACTH stimulation data were available, 94 (77%) were considered not to be adrenally sufficient (either baseline random serum cortisol < 497 nmol/L, or < 248 nmol/L increase in serum cortisol 60 minutes after the administration of 250 µg of tetracosactrin). In this study, compared with controls, the group receiving steroid replacement had reduced need for norepinephrine (mean, 1.18 AE 0.92 vs. 1.49 AE 1.29 mg per hour; p ¼ 0.03), shorter time on norepinephrine (median, 874 vs. 1,160 minutes; p < 0.0001), and a higher proportion who were able to wean norepinephrine support (33.8 vs. 9.5%; p < 0.0001).…”
Section: Adrenal Insufficiencymentioning
confidence: 99%
“…A more recent prospective multicenter cluster study of 208 neurologically deceased adults has replicated these results and further trialed steroid replacement therapy (50 mg bolus of hydrocortisone, followed by 10 mg per hour continuous infusion). 54 Of the 121 patients for whom ACTH stimulation data were available, 94 (77%) were considered not to be adrenally sufficient (either baseline random serum cortisol < 497 nmol/L, or < 248 nmol/L increase in serum cortisol 60 minutes after the administration of 250 µg of tetracosactrin). In this study, compared with controls, the group receiving steroid replacement had reduced need for norepinephrine (mean, 1.18 AE 0.92 vs. 1.49 AE 1.29 mg per hour; p ¼ 0.03), shorter time on norepinephrine (median, 874 vs. 1,160 minutes; p < 0.0001), and a higher proportion who were able to wean norepinephrine support (33.8 vs. 9.5%; p < 0.0001).…”
Section: Adrenal Insufficiencymentioning
confidence: 99%
“…The authors concluded that hydrocortisone may likely be beneficial as part of a combination regimen, but monotherapy may not impart a clinical benefit. 52 On the basis of the currently available evidence, administration of corticosteroids to the donor reduces inflammation after transplantation, but does not reduce the incidence or duration of primary graft failure. 51 Nonetheless, they have been shown to improve oxygenation, reduce extravascular lung water, increase lung yield, and reduce inflammation in the liver, heart, and kidney.…”
Section: Corticosteroid Monotherapymentioning
confidence: 99%
“…Cette stratégie pourrait néanmoins être intéressante pour le greffon pulmonaire [30,31]. D'un autre côté, une supplémentation en glucocorticoïdes à des doses plus faibles a été proposée afin de pallier l'insuffisance corticotrope induite par la ME, dans le but d'améliorer la défaillance hémodynamique du potentiel DDME [33,65]. Dans l'étude française CORTICOME récemment publiée, une supplémentation en hydrocortisone (50 mg puis 10 mg.h -1 jusqu'au clampage aortique) chez des potentiels DDME, s'accompagnait d'une diminution des posologies de noradrénaline nécessaires et d'un sevrage plus fréquent de celle-ci, en comparaison à un groupe témoin ne recevant pas d'hydrocortisone [65].…”
Section: Vasopressineunclassified
“…D'un autre côté, une supplémentation en glucocorticoïdes à des doses plus faibles a été proposée afin de pallier l'insuffisance corticotrope induite par la ME, dans le but d'améliorer la défaillance hémodynamique du potentiel DDME [33,65]. Dans l'étude française CORTICOME récemment publiée, une supplémentation en hydrocortisone (50 mg puis 10 mg.h -1 jusqu'au clampage aortique) chez des potentiels DDME, s'accompagnait d'une diminution des posologies de noradrénaline nécessaires et d'un sevrage plus fréquent de celle-ci, en comparaison à un groupe témoin ne recevant pas d'hydrocortisone [65]. S'il est difficile de recommander l'administration d'une corticothérapie à forte dose systématique par hydrocortisone dans le contexte de la ME, celle-ci peut être considérée chez le sujet en ME instable sur le plan hémodynamique et nécessitant des posologies élevées de noradrénaline pour maintenir les objectifs de réanimation.…”
Section: Vasopressineunclassified